EFFECTIVENESS OF DIAMMONIUM PHOSPHATE IMPREGNATED WITH PSEUDOMONAS PUTIDA FOR IMPROVING MAIZE GROWTH AND PHOSPHORUS USE EFFICIENCY - S. Noor; M. Yaseen; M. Naveed; R. Ahmad (Journal of Animal and Plant Sciences, 2017)
Use efficiency of soil applied phosphatic fertilizers in calcareous soils is less than 25%. Phosphorus from these fertilizers becomes fixed or precipitated by Ca+2 and Mg+2 in such soils. This efficiency can be improved by using phosphorus-solubilizing bacteria (PSB). A pot study was conducted to investigate the comparative impact of different levels of diammonium phosphate (DAP) fertilizer impregnated with Pseudomonas putida biotype A (Q7) on growth attributes and phosphorus use efficiency (PUE) of maize in comparison to conventionally used DAP fertilizer. The culture of pre-isolated phosphate solubilizing bacterial strain Q7 was used to impregnate phosphatic fertilizers with the help of molasses used as carbon source. In general, microbial inoculation is known to be effective for enhancing nutrient use efficiency. However, results showed that impregnated phosphatic fertilizer (DAP) improved maize growth and dry matter yield up to 12% over conventional DAP fertilizer. Use efficiencies of impregnated DAP i.e. up to 62% increase of agronomic efficiency and 8% increase of physiological efficiency over control. Similarly, phosphors uptake was also increased with impregnated DAP by 33% over conventional DAP application. Results may imply that impregnation of DAP fertilizer could be a novel approach for improving growth and P - use efficiency of maize crop.
Keywords: Impregnation; maize; DAP; PUE; Pseudomonas putida